Improving the Quality of Human Resources through the Application of Good Psychology and Human Capital - Widarni, Eny Lestari; Bawono, Suryaning (Asia Pacific Journal of Management and Education (APJME), 2022)
We'd want to look at existing research ideas on the aspects that lead to positive psychology, as well as the advantages of boosting the quality of human resources and human capital for economic growth. We gather scientific publications from Emerald, Science Direct, Sciendo, and Korean science, as well as books written by psychologists and economists, using Content Analysis. Human capital is an important thing that always exists in life around the world, human capital must and can be measured in quality, but there are challenges in developing human capital, namely: lack of operational definitions and value assessment of human resources owned, process complexity, subjectivity in its application, and the inconsistent information needs of administrators. In a buying and selling business, there are also unique characteristics, namely the lack of structure, the importance of persuasion and the development and maintenance of good relationships, things like this greatly affect the performance of Human Resources. Another thing that can affect the quality of your Human Resources is psychology. Employees who have good psychology tend to find it easier to get a job and get a salary which results in the economic stability of each individual and a country.